Mental health professionals recognizing animals as victims - Randour, Mary Lou (Animals as crime victims, 2024)
Mental health professionals have been trained to be alert to the possibility that abuse or neglect may be occurring in an individual’s relationships or in a family. Despite growing awareness of the importance of the human-animal bond in the lives of many, research indicates that mental health professionals infrequently ask about an individual’s relationships with animals. Asking questions about the animals in an individual’s life can reveal that frequently animals are voiceless victims in a situation and that the animal’s plight needs to be addressed. This chapter investigates possible factors that prevent mental health professionals from inquiring about companion animals, such as not knowing what questions to ask or not feeling equipped to handle the information they learn. It then suggests changes in policies, as well as professional norms and practices, which would encourage mental health professionals to identify and respond to animal victimhood.